2008
DOI: 10.1002/anie.200705303
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Platensimycin

Abstract: In modern drug discovery, antibodies or libraries of simple synthetic organic compounds, mostly of heterocyclic origin, are favored. Natural products play an increasingly inferior role as they are considered structurally too complex, limited in quantity, and difficult to synthesize, manipulate, and derivatize. Thus it was a sensation when a Merck research group reported that classical screening of metabolites from Streptomyces platensis has unearthed a low-molecular-weight organic compound with remarkable anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(61 citation statements)
references
References 51 publications
0
57
0
Order By: Relevance
“…Indeed, the novel scaffold and intriguing biological property of platensimycin captured the interest of several research groups, which reported different elegant total syntheses. 55 In addition, medicinal chemistry studies have been conducted, and the design, synthesis and biological evaluation of several platensimycin analogs incorporating varying degrees of molecular complexity have been reported. [56][57][58] Preliminary Antibiotic discovery in the twenty-first century S Donadio et al data indicate that certain modifications of the intricate cage region can be made without detrimental effects on potency, whereas even small modifications of the benzoic acid region result in a drastic loss of activity ( Figure 1).…”
Section: Chemical Derivativesmentioning
confidence: 99%
“…Indeed, the novel scaffold and intriguing biological property of platensimycin captured the interest of several research groups, which reported different elegant total syntheses. 55 In addition, medicinal chemistry studies have been conducted, and the design, synthesis and biological evaluation of several platensimycin analogs incorporating varying degrees of molecular complexity have been reported. [56][57][58] Preliminary Antibiotic discovery in the twenty-first century S Donadio et al data indicate that certain modifications of the intricate cage region can be made without detrimental effects on potency, whereas even small modifications of the benzoic acid region result in a drastic loss of activity ( Figure 1).…”
Section: Chemical Derivativesmentioning
confidence: 99%
“…Bisboronic esters (31-34) also gave access to alkenyl-monoboronic esters, given the higher reactivity of the terminal boron group allowing chemoselective SuzukiMiyaura couplings. Therefore, several alkenyl boronates were prepared (35)(36)(37)(38)(39)(40)(41)(42) in which the terminal boron was replaced by various residues. Subjecting substrates 35-40 to the iridium-catalyzed hydrogenation excellent selectivities ranging from 95% to 99% ee were achieved.…”
Section: Development Of New Catalystsmentioning
confidence: 99%
“…[35] After Nicolaou reported the first total synthesis of racemic Platensimycin in 2006, [36] several research groups have been involved in an asymmetric approach to it. [37] Among them the Mulzer group has recently reported an elegant approach, [38] which involves two hydrogenation reactions as key synthetic transformations.…”
Section: Applications In the Synthesis Of Complex Moleculesmentioning
confidence: 99%
“…17 Platencin core structure constitutes tricyclic system with a bicyclic octane ring having exomethylene group, fused with a cyclohexenone ring. Many synthetic strategies have been developed for the construction of platencin core structure involving key steps like homoallyl radical rearrangement of bicyclo[3.2.1]octane to bicyclo[2.2.2]octane, [18][19][20][21][22] intramolecular DielsAlder reaction, [22][23][24] intramolecular Michael addition, 25 Michael addition followed by aldol condensation, 26 ring closing metathesis reaction, 27,28 pinacol coupling reaction, 29 radical cyclization reactions [30][31][32][33] and intramolecular aldol reaction. 34 Although nor-platencin is less potent than its parent molecule, but serves as a convenient target as it lacks the acid-sensitive exo-methylene group present in platencin which is also responsible for the decrease in the metabolic stability of platencin.…”
Section: Introductionmentioning
confidence: 99%